Underwater digital elevation map gridding method based on optimal partition of suitable matching area. (26th March 2019) - Rupeng, Wang; Ye, Li; Teng, Ma; Zheng, Cong; Yusen, Gong
Global positioning system signal does not penetrate into the water volume, and autonomous underwater vehicle have to use the inertial navigation system that will cause an inevitable cumulative error. Terrain reference position can zero out the inertial navigation system error and have been widely used. To improve the positioning accuracy, the planning path of the underwater robot is required to pass through the suitable matching areas in the path planning stage. So, a gridding map is needed to quantify the suitability of the terrain and to partition the suitable matching area and the unsuitable matching area optimally. In this article, we will focus on the quantitative method of terrain suitability and the grid parameter solution method for optimal partition of suitable matching area. Finally, the validity of the algorithm is obtained using the ship borne data. The results show that in the low suitability blocks, the influence of measurement error on terrain reference position accuracy is higher than that in high suitability blocks. And the average of terrain reference position deviation obtained of the path passed through the high suitability area is 53.3% which is lower than that of the path passed through the low suitability area, and the standard deviation of the position deviation is reduced by 21.15%.